Condition Assessment of Fire-Affected RC Slab Via GPR Signal Reflections Analysis and Visual Inspection Method - F.Senin, S.; Azilawati Abu Talaha, Nor; Hamid, R. (International Journal of Engineering and Technology, 2019)
This study aims to assess the condition of a fire-damaged building for recommendation of repair works. The Institute of Medical Research (IMR) building, in Kuala Lumpur, Malaysia was damaged by fire in April 2011.Visual inspection (VI) is the normal assessment method, but for more accurate results, Ground Penetrating Radar (GPR) signal reflections analysis is employed. The defects analyzed are cracks and delamination of the affected area which was the reinforced concrete (RC) slab at level 3, location where the fire had started. The results obtained using GPR and visual inspection were compared. The area where cracks were detected visually was confirmed by results from the GPR signal reflections analysis but visually, only 28% of the slab area showed delamination defect. When checked with GPR, the area of delamination was actually 56 % of the slab area. Cracks and delamination damage mapping was prepared in order to help facilitate repair works. This result shows that Ground Penetrating Radar (GPR) signal reflections analysis had detected delamination in RC slab where normal visual inspection failed to detect.